The 46 rules of genius : an innovator's guide to creativity - Neumeier, Marty (Voices that matter., 2014)
Not since Strunk and White's ELEMENTS OF STYLE has a book compressed so many insights into so few pages. With his trademark simplicity and wit, Marty Neumeier has written and illustrated a concise guide that can be read quickly over a lunch break or savored slowly over a lifetime. Part 1, "How can I innovate?" offers insightful guidance such as "Feel before you think," "See what's not there," and "Ask a bigger question." Rule #1 gives the paradoxical advice: "Break the rules." Part 2, "How should I work?" offers down-to-earth tips on craft: "Use a linear process for static elements," and "Express related elements in a similar manner." The reader is also reminded: "Don't be boring!" In Part 3, "How can I learn?" contains practical advice including "Do your own projects," "Invest in your originality," and "Develop an authentic style." Finally, Part 4, "How can I matter?" deals with the deeper questions of a career in creativity, such as "Overcommit to a mission," "Build support methodically," and "Become who you are." THE 46 RULES OF GENIUS is a reassuring lighthouse against the swirling tides of innovation. Geniuses from every discipline will want to keep it in sight. (Educators: Those who recommend this book to students may also be interested its deeply researched precursor, METASKILLS, from which the rules were drawn.) From the back cover: There's no such thing as an accidental genius. Anyone who's reached that exalted state has arrived there by design. But simply wanting to get there is not enough. A would-be genius also needs a theoretical framework, a basic compass, a set of principles to guide the way forward. Marty Neumeier, acclaimed author of The Brand Gap and Metaskills, has compressed the wisdom of the ages into the first "quick start guide" for genius -- 46 glittering gems that will light your path to creative brilliance. This is THE essential handbook for designers, entrepreneurs, marketers, educators, artists, scientists, innovators, and future leaders in every field